HARNESSING INNOVATION POTENTIAL OF CROWDSOURCING - Slavica ROCHESKA; Marjan ANGELESKI; Dimitar NIKOLOSKI; Gjorgji MANCHESKI (Challenges of the Knowledge Society, 2014)
The new innovation paradigm is based upon articulation of external and internal sources of innovation. Nowadays, crowdsourcing is coming up as significant external source in innovation processes of the companies. Crowdsourcing enables harnessing of initiatives, ideas, solutions and knowledge of the crowd so as to enhance innovation performance and induce a value creation. Given that existing innovation literature does not cover sufficiently the issues related to crowdsourcing this paper is to offer an additional views about innovation potentials of crowdsourcing thus contributing for future research on this relatively unexplored concept. Therefore, this paper aims at considering key insights about crowdsourcing contribution on developing companies’ innovation capacity. More specifically it is focused on identification of benefits, weaknesses and risks arising from crowdsourcing to the innovation process comprising conceptual and empirical aspects.